The images of the Orthodox and the Catholics in the historical novel “The Princess of Ostrog” by Vs. S. Solovyov: Образы православных и католиков в историческом романе Вс. С. Соловьёва «Княжна Острожская» - Karpina, Elena (Przegląd Wschodnioeuropejski, 2020)
The article is dedicated to the study of the religious problems of Vs. S. Solovyov’s historical novel “The Princess of Ostrog”, the central plot conflict of which is an open struggle between the Orthodoxy and the Catholicism that broke out in the 16th century in The Polish- Lithuanian Commonwealth. In the process of analysing the designated aspect of the text the author comes to the conclusion that the images of Konstantin, Halshka and Beata Ostrozhsky considered in the paper are a clear embodiment of the three possible life aspirations of the people who lived in the era recreated by the author: the struggle for the Orthodoxy in the Grand Duchy of Lithuania; asserting one’s right to profess the Orthodoxy; propaganda of the Catholicism.